Measuring Trends in Access to Modern Infrastructure in Sub-Saharan Africa : Results from Demographic and Health Surveys - Banerjee, Sudeshna; Diallo, Amadou Bassirou; Wodon, Quentin (World Bank, Washington, DC, 2012)
A recent study for sub-Saharan Africa by Banerjee et al. (2007) uses Demographic and Health Surveys (DHS) from 22 countries that have conducted at least two such surveys between 1990 and 2005 in order to collect comparable information across countries on access to modern and alternative infrastructure services over time. In addition to national, urban, and rural trends in access, the study includes a distributional analysis of how access rates have evolved since 1990. That is, households are divided into five quintiles of population according to their level of wealth, with wealth defined using a principal components analysis. The objective of this note is to provide a summary of key findings from the study regarding access trends to electricity, piped water, flush toilets, and landline telephones over the period 1990-2005.